Psychosocial Impact of Brain Injury: A Review - Kumar, Raj; Kumar, Arushi; Singh, Amit Kant (Indian Journal of Neurosurgery, 2019)
Traumatic brain injury (TBI) is known as “silent epidemic” because of lack of knowledge about it and its delayed symptoms of memory and cognitive problems. The incidence is approximately 1.4 million per year in the United States, and in the developing countries, it is approximately 341 per 100,000. In the United States, the annual productivity loss due to TBI and its delayed effects is more than $56 billion. TBIs occur mainly due to traffic accidents and falls. All the age groups are affected, but the rates are higher in men than in women. The causes vary as per the age groups as traumas affect mainly children and elderly, and traffic accidents and violence affect more of adolescents and young adults. Data from various studies indicate wide variation in the incidence and prevalence of psychiatric disorders after TBI, but they are definitely higher as compared with general population. We also noted different psychiatric disorders in post head injury cases during follow-up at our university hospital, which included depression, behavioral disorders, cognitive disorders, memory impairment, anxiety disorders, stress-related headache, vertigo, irritability and sleep disorders, etc. Therefore, this review was undertaken to assess the psychosocial impact of brain injury on an individual.
Keywords: traumatic brain injury; psychiatric disorders; psychological effects; social effects